Analisis Faktor-Faktor Yang Mempengaruhi Keputusan Membeli Smartphone Produk China (Studi Kasus Pada Mahasiswa Fakultas Ekonomi Dan Bisnis Universitas Muhammadiyah Surakarta) - Sundara, Sadewa Bayu; , Drs. Kusdiyanto, M.Si (2015)
The purpose of this study was to obtain empirical evidence about whether the variable price and quality individually and together have a significant influence on the purchase decision Smartphone products from China. Based on the results of the study are expected to be used as consideration for Smartphone brands of Chinese products to take an appropriate policy strategies in order to win the competition in the field of Smartphone products. The number of samples taken by 100 respondents using purposive sampling method. Based on the results of t test analysis unknown variable price has a significant influence on purchasing decisions and the quality has a significant influence on the decision pembelian.Hasil obtained F-test analysis of F> F table (65.381> 4.00), then Ho is rejected, Means together variable price and quality together to the purchasing decision. So that the model used is fit.Sedangkan calculation results for the R2 value obtained in multiple regression analysis obtained with a coefficient of determination adjusted-R2 of 0.565. This means that 56.5% of variation variable purchase decision can be explained by the variable price and quality while the remaining 43.5% is explained by other factors outside the model studied. Based on these results that the most dominant factor in influencing the purchasing decision is the price factor. This is because the price has a value of 8.981 thitungsebesar compared with other variable is the quality factor of 5.924. Keywords: Price, Quality and Purchase Decision.